Takhrij and Syarah of Chemistry: Perspective Hadith and Science About Black Cumin as an Herbal Remedy - Diar Sabda Sabiqul Husna; Nurul Mawahda Iskandar; Soni Setiadji; Wahyudin Darmalaksana; Engkos Kosasih (Gunung Djati Conference Series, 2021)
The purpose of this study was to discuss the hadith of the Prophet Muhammad about Habbatus Sauda’ plant (Black cumin). The qualitative research method uses the takhrij and sharah hadith approaches with chemical analysis. The results and discussion of this study are Habbatus Sauda’ plant is popular in Prophet Muhammad period, and well-known in modern medicine, and is clinically proven can be used as an herbal remedy. The conclusion of this study is the takhrij and syarah hadith of the Prophet SAW regarding Habbatus Sauda’ plant in perspective hadith and science as herbal remedy.